2021
DOI: 10.1186/s40842-021-00122-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Covid-19 quarantine on diabetes Care in Children

Abstract: Background With the onset of the COVID-19 pandemic and state-mandated school closures in the spring of 2020, the management of type 1 diabetes in children underwent significant changes. The aim of our study was to assess the effect of stay-at-home orders on glycemic control in children. Methods We conducted a retrospective review of 238 children with type 1 and type 2 diabetes who were seen in the Pediatric Endocrinology Clinic at the University of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Individuals will continue to experience fast metabolic decompensation, resulting in DKA, if the diagnosis of DM1 is delayed [ 136 ], as we saw during the COVID-19 pandemic. DKA is linked to increased morbidity and death, and our metanalysis suggests the necessity for focused public awareness efforts aimed at preventing DKA upon DM1 diagnosis by recognizing and treating symptoms early.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals will continue to experience fast metabolic decompensation, resulting in DKA, if the diagnosis of DM1 is delayed [ 136 ], as we saw during the COVID-19 pandemic. DKA is linked to increased morbidity and death, and our metanalysis suggests the necessity for focused public awareness efforts aimed at preventing DKA upon DM1 diagnosis by recognizing and treating symptoms early.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has led to an economic crisis, and those whose financial stability was already difficult were first to suffer[ 37 ]. Researchers found that minority children had a higher glycosylated hemoglobin (HbA1c) level both in the pre-pandemic and the lockdown period than white race[ 38 - 40 ]. Similarly, patients with medical aid had a notably higher HbA1c and increase in HbA1c during the lockdown than those with private insurance[ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that minority children had a higher glycosylated hemoglobin (HbA1c) level both in the pre-pandemic and the lockdown period than white race[ 38 - 40 ]. Similarly, patients with medical aid had a notably higher HbA1c and increase in HbA1c during the lockdown than those with private insurance[ 38 ]. Other publications have also indicated that youth whose families are in a disadvantaged financial condition have poorer glucose control[ 38 - 40 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations